Important reductions in the global number of MERS cases and deaths since 2016 - Donnelly, C; Malik, M; Elkholy, A; Cauchemez, S; Van Kerkhove, M (Centers for Disease Control and Prevention, 2019)
Since 2012, Middle East respiratory syndrome (MERS) coronavirus has infected 2,442 persons worldwide. Case-based data analysis suggests that since 2016, as many as 1,465 cases and 293–520 deaths might have been averted. Efforts to reduce the global MERS threat are working, but countries must maintain vigilance to prevent further infections.